Adoption of Improved Dairy Management Practices by the Women Dairy Farmers in Deoghar District of Jharkhand - Sudhanshu, Sudhanshu (Indian Journal of Extension Education, 2021)
Study was conducted in the Deoghar district of the Santhal region of Jharkhand state to ascertain the extent of adoption of improved dairy management practices by the women dairy farmers. Five villages with maximum women dairy farmers from Deoghar block, and each village, 24 women dairy farmers were selected randomly. It was observed that the majority of the respondents (93.30%) ensure a sufficient supply of clean and fresh water to the animal, 75.83 per cent have awareness of heat symptoms, 86.60 per cent segregation of sick animals from healthy ones and 80.83 per cent were aware about keeping animals loose in the shed. It was also observed that the majority (56.66%) of respondents have a medium level of adoption of improved dairy management practices, followed by 22.5% of respondents have a low level of adoption, and 20.83 per cent have a high level of adoption of improved dairy management practices.